Intraclonal Genome Stability of the Metallo-β-lactamase SPM-1-producing Pseudomonas aeruginosa ST277, an Endemic Clone Disseminated in Brazilian Hospitals - Nascimento, Ana P. B.; Ortiz, Mauro F.; Martins, Willames M. B. S.; Morais, Guilherme L.; Fehlberg, Lorena C. C.; Almeida, Luiz G. P.; Ciapina, Luciane P.; Gales, Ana C.; Vasconcelos, Ana T. R. (Frontiers in Microbiology, 2016)
Carbapenems represent the mainstay therapy for the treatment of serious P. aeruginosa infections. However, the emergence of carbapenem resistance has jeopardized the clinical use of this important class of compounds. The production of SPM-1 metallo-β-lactamase has been the most common mechanism of carbapenem resistance identified in P. aeruginosa isolated from Brazilian medical centres. Interestingly, a single SPM-1-producing P. aeruginosa clone belonging to the ST277 has been widely spread within the Brazilian territory. In the current study, we performed a next-generation sequencing of six SPM-1-producing P. aeruginosa ST277 isolates. The core genome contains 5 899 coding genes relative to the reference strain P. aeruginosa PAO1. A total of 26 genomic islands were detected in these isolates. We identified remarkable elements inside these genomic islands, such as copies of the blaSPM-1 gene conferring resistance to carbapenems and a type I-C CRISPR-Cas system, which is involved in protection of the chromosome against foreign DNA. In addition, we identified single nucleotide polymorphisms causing amino acid changes in antimicrobial resistance and virulence-related genes. Together, these factors could contribute to the marked resistance and persistence of the SPM-1-producing P. aeruginosa ST277 clone. A comparison of the SPM-1-producing P. aeruginosa ST277 genomes showed that their core genome has a high level nucleotide similarity and synteny conservation. The variability observed was mainly due to acquisition of genomic islands carrying several antibiotic resistance genes.